ANALISIS PENGELOLAAN PANGKALAN PENDARATAN IKAN (PPI) MACCINI BAJI KABUPATEN PANGKAJENE DAN KEPULAUAN - Asrayanti Mustakim; Danial Danial; Ihsan Ihsan (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2018)
Asrayanti As. Management Analysis of Maccini Baji Fish Landing Bases in Pangkajene and Kepulauan Regency. Guided by Danial and Ihsan. Study aims to analyze the improvement of the functions and infrastructure facilities of PPIs and formulate management strategies. This research was conducted in May to July 2018. The survey method was supported by primary and secondary data with a Purposive Sampling system. Data analysis is utilization analysis and SWOT analysis. The results showed that the facilities contained in the PPI Maccini Baji for pond ponds need to be dredged as deep as 2.25 m because they have a shallow depth of 0 meters at the lowest tide. Meanwhile, the dock is still in the form of a revetment so that in the future it is necessary to build a pier. Ice Factory Facilities and SPDN also still require additional stock to meet all the requirements around the PPI. From the results of the SWOT analysis showing the coordinates of 1.4: 1.25 which are in the quadrant I position or aggressive strategy, this condition is to support an aggressive growth policy (growth oriented strategy) by maximizing every strength possessed and utilizing existing opportunities. Strategic steps that can be taken are; developing an effective marketing system and improving service and convenience for fishermen who utilize PPI, as well as integrated licensing.